Capecitabine-related death in triple negative breast cancer: a case report - Mauro Miranda Veloso Júnior, Gerson; Cristina Souza do Espírito Santo, Andreza; Simonsen Augusto de Carvalho Caetano, Djenanne; da Costa Souza, Juliana (Mastology, 2025)
Triple-negative breast cancer (TNBC) is an immunohistochemical subtype of breast neoplasia characterized by the absence of hormonal receptor and HER2 expression. Capecitabine has been increasingly used in the treatment of TNBC patients who did not achieve a pathological complete response (pCR) after neoadjuvant therapy, showing favorable survival outcomes. Adverse effects related to capecitabine use are common, including gastrointestinal, hematologic, and dermatologic toxicity. However, the drug is generally well tolerated, and fatal outcomes related to treatment are infrequent. Due to its atypical nature, this study reports a death associated with therapy. In the case presented, the patient developed pancytopenia and febrile neutropenia (FN) 18 days after starting chemotherapy, progressing to alveolar, gastrointestinal, vaginal, and urethral hemorrhage, followed by hemodynamic instability, cardiopulmonary arrest, and death. Mortality occurring so early after capecitabine initiation may be linked to genetic alterations in certain individuals, such as dihydropyridine (DPD) deficiency. Genetic testing to identify DPD gene defects could allow for chemotherapy dose adjustments and reduce toxicity prevalence; however, such testing is not routinely performed. Further studies are needed to substantiate and assess the degree of benefit of this investigation before capecitabine chemotherapy, as well as the appropriate course of action based on the results. In these patients, FN prophylaxis with recombinant granulocyte colony-stimulating factors (G-CSFs) may also be considered, although it is primarily recommended for chemotherapeutic agents with a higher risk of myelotoxicity. Additional research is necessary regarding the actual application of capecitabine in TNBC cases to evaluate effectiveness, tolerability, and improve patient management.